Approximate array multipliers - Balasubramanian, Padmanabhan (2021)
This article describes the design of approximate array multipliers by making vertical or horizontal cuts in an accurate array multiplier followed by different input and output assignments within the multiplier. We consider a digital image denoising application and show how different combinations of input and output assignments in an approximate array multiplier affect the quality of the denoised images. We consider the accurate array multiplier and several approximate array multipliers for synthesis. The multipliers were described in Verilog hardware description language and synthesized by Synopsys Design Compiler using a 32/28-nm complementary metal-oxide-semiconductor technology. The results show that compared to the accurate array multiplier, one of the proposed approximate array multipliers viz. PAAM01-V7 achieves a 28% reduction in critical path delay, 75.8% reduction in power, and 64.6% reduction in area while enabling the production of a denoised image that is comparable in quality to the image denoised using the accurate array multiplier. The standard design metrics such as critical path delay, total power dissipation, and area of the accurate and approximate multipliers are given, the error parameters of the approximate array multipliers are provided, and the original image, the noisy image, and the denoised images are also depicted for comparison.